Severe metabolic acidosis due to acetazolamide intoxication in a dog. Issue 1 (6th October 2020) - Johnston, L; Leister, E; Singer, L
Abstract : Case report: This case report describes the clinical signs and case management of a 1‐year‐old neutered male Siberian Husky that accidentally ingested 635 mg/kg of oral acetazolamide (a carbonic anhydrase inhibitor). The dog presented with severe tachypnoea due to the development of hyperchloraemic metabolic acidosis and associated hypokalaemia that persisted for 7 days. Clinical and biochemical changes resolved with intravenous and subsequent oral supplementation of sodium bicarbonate and potassium. Complete recovery occurred within 9 days of presentation. Conclusion: To the authors' knowledge, this is the first case that reports overdosage of an oral carbonic anhydrase inhibitor in a dog and subsequent recovery with adequate supplementation and supportive care.